2013
DOI: 10.1371/journal.pone.0060487
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Length of Hospital Stay among HIV Positive and HIV Negative Patients with Tuberculosis in Brazil

Abstract: ObjectiveIdentify and analyze the factors associated to length of hospital stay among HIV positive and HIV negative patients with tuberculosis in Manaus city, state of Amazonas, Brazil, in 2010.MethodsEpidemiological study with primary data obtained from monitoring of hospitalized patients with tuberculosis in Manaus. Data were collected by interviewing patients and analyzing medical records, according to the following study variables age, sex, co-morbidities, education, race, income, lifestyle, history of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“… 17 In addition, tuberculosis is also associated with longer LOS both among the general and the HIV-infected population. 18 , 19 In our study cohort, tuberculosis accounted for 43% of all AIDS related hospitalizations and yielded an inhospital mortality of 10.9% (data not shown). Additionally, LOS of tuberculosis related hospitalization was significantly longer than non-tuberculosis hospitalizations (median of 18 days vs. 12 days, respectively, p < 0.001, data not shown).…”
Section: Discussionmentioning
confidence: 63%
“… 17 In addition, tuberculosis is also associated with longer LOS both among the general and the HIV-infected population. 18 , 19 In our study cohort, tuberculosis accounted for 43% of all AIDS related hospitalizations and yielded an inhospital mortality of 10.9% (data not shown). Additionally, LOS of tuberculosis related hospitalization was significantly longer than non-tuberculosis hospitalizations (median of 18 days vs. 12 days, respectively, p < 0.001, data not shown).…”
Section: Discussionmentioning
confidence: 63%
“…This finding may indicate that comorbidities contributed to a more severe condition that required hospitalization [ 26 ]. In the previous research, patients with TB and comorbidities, particularly renal and liver diseases, diabetes mellitus, HIV, or cancer, were more likely to be hospitalized and have longer inpatient treatment [ 8 , 26 , 27 , 28 ]. Similarly, we found that patients with UGTB and hepatitis B were more likely to stay longer in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated hospital admissions were not common in our study population, which is consistent with previous research. Patients usually start TB treatment in-hospital and initial hospitalization contributes the most to the total length of stay during treatment [ 8 , 28 ]. Research in the United States and Canada, countries that prioritize reduction of hospital admissions, showed similar proportions of patients with TB with multiple hospitalization episodes during treatment (7 and 8%, respectively) [ 8 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study that retrospectively evaluated the effect of various factors on hospital LOS in Louisiana, USA between 1998 and 2003, reported that gender and age were non-significant predictors, while the number of comorbid conditions and inpatient procedures and the presence of an AIDS defining diagnosis were significant independent predictors [11]. Another study conducted in Brazil, reported that low income was associated with prolonged LOS among HIV-positive patients with tuberculosis [12]. In comparison to the findings of some of the above studies, tuberculosis, multiple organ involvement (�3 organ systems) and in-hospital mortality were associated with a longer LOS on univariate analysis, while there were no significant differences with regards to age, gender, low CD 4 cell count (<100 cell/mm 3 ), use of ART and Pneumocystis jirovecii pneumonia.…”
Section: Plos Onementioning
confidence: 99%
“…There is a paucity of published data pertaining to factors that predict the length of hospitalization in HIV-positive patients presenting to the ED [11,12]. In addition to guiding clinical management, the identification of these factors may assist clinicians with triage and the appropriate channeling of resources, particularly in resource limited environments.…”
Section: Introductionmentioning
confidence: 99%